A case of mucoepidermoid carcinoma of the bronchus presented with hydropneumothorax in a child. Issue 3 (25th October 2013) - Kose, Mehmet; Bilgin, Mehmet; Kontas, Olgun; Ozturk, Sedat; Doganay, Selim; Ozdemir, Mehmet Akif
Summary Mucoepidermoid carcinoma is a rare pulmonary neoplasm seen in the pediatric population. We report a low grade mucoepidermoid carcinoma in a 12‐year‐old boy who presented with spontaneous pneumothorax. Pediatr Pulmonol. 2014; 49:E86–E89. © 2013 Wiley Periodicals, Inc.